ANALYSIS OF CR, DER, TAT ON PROFIT GROWTH IN TRADING SECTOR COMPANIES - Yois Nelsari Malau; Angel Elizabeth Siregar; Emy Sartika Ginting (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The purpose of this study was to determine and analyze the effect of Current Ratio, Debt to Equity Ratio, Total Assets Turnover, Net Profit Margin on profit growth. The data in this study were taken from the annual report data source on the Indonesia Stock Exchange through the idx.co.id website and have been carried out based on the existing sample criteria. This research method uses quantitative methods. Data collection method using secondary data. The sampling technique applies purposive sampling. The population in this study is 47 financial statements of trading sector companies in 2017-2019 which are listed on the Indonesia Stock Exchange. And the number of samples in the study is 39. Based on this research, it shows that partially the variables that affect profit growth are Debt to Equity Ratio and Total Assets Turnover, while variables that do not affect profit growth are Current Ratio and Net Profit Margin.